The influence of transgression and consumer anger on service providers’ evaluation (Signos do Consumo, 2015)
The overall purpose of this research was to verify the influence of the anger emotion in consumers, resulting from a transgression situation (violation of conduct, failure), on the perception of quality of the consumer-company relationship. The research also analyses the efficiency of recovery actions. Anger appeared as the most felt emotion after the service failures, and after the recovery actions, the averages of negative emotions fell, specially the averages of anger.